ANALISIS PROMOSI MEDIA SOSIAL INSTAGRAM TERHADAP KEPUTUSAN BERKUNJUNG WISATAWAN DI DESA WISATA BATULAYANG: The Analysis of Instagram Social Media Promotion on Tourists’ Visiting Decisions in Batulayang Tourist Village - Tiara Rahma Asyar; Dhanik Puspita Sari (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Bogor, 2025)
Nowadays, for promotional outreach, many people use social media, such as Instagram and other social communication platforms. The use of the internet has brought information closer through people's activities through social media, and is currently widely used as a medium in promoting both goods and services for economic purposes. One component of the marketing mix, or marketing mix, is promotion. This study aims to determine the effect of Instagram social media promotion on tourist decisions to visit Batulayang Tourism Village. This research uses quantitative methods with a sample of 104 respondents. This sampling technique uses purposive sampling. The data collection technique uses a questionnaire that has been designed. The power analysis method used is simple linear regression, which includes validity test, reliability test, normality test, T test, and coefficient of determination (R2) test. The authors analyzed the data using SPSS Statistics 29. The results showed that Instagram social media promotion had an effect on visiting decisions. With the determination test results of 59.9 % influenced by these variables, and the rest is influenced by other variables not examined in this study. The conclusion is that Instagram social media promotion has a significant influence on visiting decisions through promotions provided by Batulayang Tourism Village to meet the needs of visitors when visiting.